China's Spatial Economic Network and Its Influencing Factors. (30th December 2020) - Yu, Guihai; He, Deyan; Lin, Wenlong; Wu, Qiuhua; Xiao, Jianxiong; Lei, Xiaofang; Xie, Zhongqun; Wu, Renjie
Abstract : With the deepening of reform and opening-up, China's economy has been further developed, but there is still a problem of uneven development. It is of great significance to completely construct China's economic spatial correlation network, to clarify the role and status of each province in the whole network, and to study the influencing factors of the national spatial economic network. In this paper, we employ the network analysis method to analyze China's economic development in the past 20 years. Based on the modified gravity model, we construct China's spatial economic network and explore the network structure from three aspects: the whole network structure feature, characteristics of individual provinces in the network, and block model analysis. The results show that (1) China's spatial economic network has strong internal cohesion, and the hierarchy of the network is becoming less and less obvious. However, the network density is low, and the overall network relationship still needs to be strengthened. (2) The different levels in economic development illustrate the obvious economic unbalance among provinces. (3) The block model analysis results demonstrated that coastal areas are more attractive to other provinces and are playing an important role in driving China's economy. Finally, we employ Quadratic Assignment Procedure (QAP) regression analysis to analyze the influential factors on spatial economic network. Numerical results show that the geographic proximity and the differences in six factors (industrial structure, level of economic development, degree of opening to the outside world, medical level, size of labor market, and infrastructure) have significant impact on the spatial economic network. Moreover, the influence of these factors on the economic relation among provinces has been gradually strengthened in recent years.